(untitled) - Wackerhage H; Everett R; Krüger K; Murgia M; 5; Simon P; Gehlert S; Neuberger E; Baumert P; Schönfelder M (Deutsche Zeitschrift für Sportmedizin)
No health emergency in living memory has ever had greater repercussions for our health, economy and the way we live than the COVID-19 pandemic caused by SARS-CoV-2, commonly referred to as the coronavirus. COVID-19 has many links to sport and exercise: sports events such as the champions league quarter final between Atalanta Bergamo and FC Valencia on the 19.02.2020 have contributed to the virus spread; control measures such as lockdowns and closures of gyms and other sport facilities have altered our exercise behaviours; major sporting events including the Tokio Olympics have been cancelled or postponed; sports and fitness providers such as sports clubs, gyms and swimming pools have been hard hit. In this review, we will answer five questions in relation to COVID-19 fromthe perspective of sport and exercise. The questions deal with 1) how SARS-CoV-2 targets ACE2-expressing human cells via its spike protein, 2) the COVID-19 disease caused by it, 3) the COVID-19 pandemic and attempts to control it, 4) how the immune system responds to SARS-CoV-2 and how the immune system is affected byexercise training, 5) advice for exercise during the pandemic for healthy adults, athletes and elderly, and possible control measures to help to return to normal sport and exercise at the end of the pandemic before herd immunity or mass vaccination hasbeen achieved. KEY WORDS: Pandemic, Physical Activity, Detraining, Risk Group